1990
DOI: 10.1002/j.1556-6978.1990.tb01165.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Analysis of the Mental Health of Graduate Counselors in Training

Abstract: The mental health of graduate counselor trainees was examined. Trainees demonstrated more psychopathy than did the normal population on 6 of the 10 scales used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 29 publications
(20 reference statements)
0
18
1
Order By: Relevance
“…1989;McAuliffe, 1992). Studies that have examined coping resources among graduate counseling students (e.g., White & Frazoni, 1990) have found that these students score lower on measures of coping with stress than would be expected. White and Frazoni (1990) noted that the most critical question raised by these results is "What are the implications for graduate counselor training programs and the counseling field in general?"…”
mentioning
confidence: 99%
“…1989;McAuliffe, 1992). Studies that have examined coping resources among graduate counseling students (e.g., White & Frazoni, 1990) have found that these students score lower on measures of coping with stress than would be expected. White and Frazoni (1990) noted that the most critical question raised by these results is "What are the implications for graduate counselor training programs and the counseling field in general?"…”
mentioning
confidence: 99%
“…A very limited amount of research has focused on clergy who were being trained as counselors (Jansen et al 1973). The MMPI has been proposed as a resource for the prediction of graduate school performance of counselor trainees (Daehnert and Carter 1987) and as but one means of assessing the mental health of graduate counseling students (White and Franzoni 1990).…”
Section: Rationalementioning
confidence: 99%
“…This incidence of students may be explained by the findings that a proportion of students who choose such training seem to do so in order to address their own issues (Johnson and Campbell 2002;Lumadue and Duffey 1999) and that beginning graduate counselling students seem to have higher levels of psychological disturbance than the general population (White and Franzoni 1990).…”
mentioning
confidence: 98%